Direct Digital Synthesis Method and Implementation of Multi-component Signal - DENG Hong-yu; TONG Zi-quan; GAI Jian-xin; LI Zhuo-ran (Journal of Harbin University of Science and Technology)
With the traditional way to construct the complex waveform of multiple components，the large waveform storage capacity is needed and the design of the hardware circuit is complex. To solve this problem，in this paper，a method of direct waveform data synthesis of multi-component signals is studied，making full use of the hardware resource of FPGA，and establishes the basic component model of sine wave，triangle wave and pulse wave based on DDS principle，which can directly set the amplitude，frequency，phase and pulse width of each base component． Then，the multi-component waveform data is directly superimposed，and the analog waveform is generated after the digital analog conversion. Also，the relative error of direct digital synthesis of multi component signals is analyzed，and the direct digital synthesis circuit of 28 sine waves，2 triangular wave components and 2 pulse components is designed by using single chip FPGA as the carrier. The outstanding advantages of the method are that the complex waveforms can be constructed from many components． The parameters are convenient and the analog circuit is simple.